(untitled) (Bangladesh Journal of Livestock Research, 2021)
The experiment was implemented at farmer’s house and Bathan areas of Shahjadpur Upazila in Sirajganj and Bera Upazila under Pabna districts of Bangladesh. The aim of the study was to know the incidence of repeat breeding (RB), physiology of different follicles and deformity of ovary and uterus in Holstein Frisian (HF) cows. Forty (40) RB HF cows (>50% HF Genetic) were selected on the basis of age and parity. Pyometra, endo-metra, cervicitis, Salpingitis and tumor like growth etc. in uterine wall were observed. Luteal and follicular cyst was also identified. Number of growing follicle appeared ultrasonically, size of Graafian follicle, breed, cow’s body size, and inheritance level and parity, nutritional factors and days calving to first service were recorded properly. All collected data were statistically analyzed by the SPSS soft-ware program using completely randomized design (CRD). Results revealed that, significantly (P<0.05) highest Body Condition Score (BCS) was 3.47±0.05 observed in the cows of group-D whose age were more than 8 years of old compared to others group (table 1). In-case of average daily milk yield and remained dry condition differences were highly significant (P<0.001). Maximum milk yield (20.41±0.82 l/day) was observed in group-C compared to others group but minimum dry condition remaining period was observed in group-A than others. Days of heat showed number of AI service were non-significant (P>0.05) in the whole experiment (table-1). The percentage of infection (Pyometra, Endometra) in the uterine wall differed non-significantly (P>0.05) among all the groups and minimum occurrence were observed in group-A (figure 1). Highest percent of cyst observed in the right ovary than left of the cows of group-D compared to others group but the differences were non-significant (P>0.05).Comparatively higher percentage (58.82±12.30) of follicles observed in left ovary of group-D than right ovary of others group (table 3). Non-significantly (P>0.05) the highest average number (2.40±0.44) of follicles was observed in left ovary of the group-C than the cows of others group. Though the follicle size in the end of luteal phase differed non-significantly (P>0.05) but comparatively larger (14.90±1.54mm) follicle in diameter were observed in group-C, than the follicles of others groups. Bang. J. Livs. Res. Vol. 27 (1&2), 2020: P. 95-104